Synthesis, characterization, controlled release, and antibacterial studies of a novel streptomycin chitosan magnetic nanoantibiotic - Hussein-Al-Ali SH (Dove Medical Press, 2014)
Samer Hasan Hussein-Al-Ali,1 Mohamed Ezzat El Zowalaty,2,6 Mohd Zobir Hussein,3 Maznah Ismail,1,4 Thomas J Webster,5,7 1Laboratory of Molecular Biomedicine, 2Laboratory of Vaccines and Immunotherapeutics, Institute of Bioscience, 3Materials Synthesis and Characterization Laboratory, Institute of Advanced Technology, 4Department of Nutrition and Dietetics, Faculty of Medicine and Health Science, Universiti Putra Malaysia, Selangor, Malaysia; 5Department of Chemical Engineering and Program in Bioengineering, Northeastern University, Boston, MA, USA; 6Department of Environmental Health, Faculty of Public Health and Tropical Medicine, Jazan University, Jazan, 7Center of Excellence for Advanced Materials Research, King Abdulaziz University, Jeddah, Saudi Arabia Abstract: This study describes the preparation, characterization, and controlled release of a streptomycin-chitosan-magnetic nanoparticle-based antibiotic in an effort to improve the treatment of bacterial infections. Specifically, chitosan-magnetic nanoparticles were synthesized by an incorporation method and were characterized by Fourier transform infrared spectroscopy, X-ray diffraction, thermogravimetric analysis, and vibrating sample magnetometry. Streptomycin was incorporated into the nanoparticles to form a streptomycin-coated chitosan-magnetic nanoparticle (Strep-CS-MNP) nanocomposite. The release profiles showed an initially fast release, which became slower as time progressed. The percentage of drug released after 350 minutes was around 100%, and the best fit mathematical model for drug release was the pseudo-second order model. The Strep-CS-MNP nanocomposite showed enhanced antibacterial activity against methicillin-resistant Staphylococcus aureus. This study forms a significant basis for further investigation of the Strep-CS-MNP nanocomposite in the treatment of various bacterial infections. Keywords: magnetic nanoparticles, streptomycin, nanoantibiotics, chitosan, release, antimicrobial activity, methicillin-resistant Staphylococcus aureus